Physics characteristics of internally cooled annular fuel for potential application in pressure tube heavy water reactors. (February 2019) - Bromley, B.P.; Groves, K.; Colton, A.V.; Golesorkhi, S.
Highlights: Annular fuel elements in pressure tube heavy water reactors can increase power limits. Thorium-based fuels in heavy water reactors can achieve reduced coolant void reactivity. Thorium-based fuels in heavy water reactors can achieve more negative fuel temperature coefficients. The use of low enriched uranium mixed with thorium can reduce plutonium production by nearly 75%. The use of enriched zirconium in heavy water reactors can increase burnup by nearly 40%. Abstract: This paper summarizes the results of exploratory lattice physics studies of alternative, advanced fuel bundle concepts that could potentially be implemented in pressure tube heavy water reactors (PT-HWRs). The lattice physics code WIMS-AECL was used to analyze the physics performance and operational characteristics of an 18-element and a 12-element internally cooled annular fuel (ICAF) fuel bundle, made with (LEU, Th)O2 fuel, with both low-burnup and high-burnup options. Such fuel bundles with annular fuel elements may be able to operate at higher bundle power levels and with higher linear element (LER) ratings than fuel bundles with conventional solid cylindrical fuel elements. In addition, the use of thorium mixed with LEU can help extend uranium resources, exploit the energy potential in thorium, and also reduce the production of plutonium and minor actinides, due to the smaller fraction of 238 U in the fuel. The influence of improvements in the neutron economy of these lattices was also investigated, by incorporating higher-purity heavy water moderator and coolant (99.90 at.% D2 O) in the models, along with enriched zirconium (95 wt% 90 Zr/Zr) for the zirconium alloys used in the structural components. The results were compared with those for a more conventional 37-element PT-HWR fuel bundle using natural uranium (NU) fuel. Results show that annular fuels could be very attractive, being able to achieve higher burnup, comparable or better fissile utilization, reduced coolant void reactivity, and comparable or more negative fuel temperature coefficients.